PENGARUH PENERAPAN SAK EMKM DAN PEMANFAATAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN UMKM DI KABUPATEN PELALAWAN - Ameldi Putri, Dinda; Anisma, Yuneita; Riska Natariasari, Riska (Universitas Katolik Indonesia Atma Jaya, 2025)
This study aims to determine the effect of adopting Financial Accounting Standards for Micro, Small, and Medium Enterprises (FAS-MSMEs) and utilizing Accounting Information Systems (AIS) on MSMEs’ financial reporting quality in Pelalawan Regency, Riau. This study used a quantitative method and the 4 SmartPLS application to process the data. The sample consisted of 100 respondents determined using Slovin’s formula. The respondents were MSME actors operating in the capital city of Pelalawan Regency, Riau, who had been in business for at least one year and had implemented FAS-MSMEs and utilized AIS in preparing their financial statements. The results showed that FAS-MSMEs adoption and AIS use had a positive and significant effect on the FQ of MSMEs. These findings confirm that implementing accounting standards and using accounting information systems can enhance the quality of financial reporting in the MSME sector.